Assessment of mangrove species diversity in Banaybanay, Davao Oriental, Philippines - Brian Pototan; Neil Capin; Aileen Grace Delima; Annabelle Novero (Society for Indonesian Biodiversity, 2021)
Abstract. Pototan BL, Capin NC, Delima AG, Novero AU. 2021. Assessment of mangrove species diversity in Banaybanay, Davao Oriental, Philippines. Biodiversitas 22: 144-153. This study determined mangrove species diversity and community structure in Banaybanay, Davao Oriental, Philippines. Ten 150m long transects plots were laid out perpendicular through the mangrove forests yielding 30 plots and total sampled area of 3, 000 m2. Individual trees within plots were counted, identified and measured for diameter at breast height (dbh) and tree height. For diversity analysis, Shannon-Weiner Index of Diversity (H’), Pielou’s Index of Evenness (J), Simpson’s Index of Dominance (C), and Effective Number of Species (ENS) were used. Results showed a total of 33 species belonging to 14 families, 31 of which are true mangroves and two associates. Two threatened species, the endangered Camptostemon philippinensis and vulnerable Avicennia rumphiana, and three near-threatened species were recorded. Diversity analysis showed a high diversity index (H’=3.145; ENS=23) and high species evenness (J=0.85) but low dominance (C=0.05). Sonneratia alba attained the greatest importance value (IV=59.79%) due to high relative density, relative frequency, and relative dominance. Also, Rhizophoraceae is the most represented among 14 families. Hence, Banaybanay being highly diverse with the presence of threatened and near-threatened mangrove species calls for immediate protection and conservation measures because of increasing anthropogenic activities and environmental problems observed in the area.